Intimate Partner Violence and the Risk of Developing Fibromyalgia and Chronic Fatigue Syndrome - Chandan, Joht Singh (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is a global public health issue with a variety of ill health consequences associated with exposure. Due to the stimulation of chronic stress and inflammatory pathways, childhood abuse has been associated with the subsequent development of functional syndromes such as fibromyalgia and chronic fatigue syndrome (CFS). Although IPV in women appears to elicit similar biochemical responses, this association has not been tested thoroughly in IPV survivors. These functional syndromes are complex in etiology and any indication of their risk factors would benefit health care professionals managing this population. Therefore, we aimed to investigate the association between exposure to IPV with functional syndromes: fibromyalgia and CFS. We conducted a retrospective open cohort study using “The Heath Improvement Network” database between January 1, 1995 and December 1, 2017. A total of 18,547 women who were exposed to IPV were each matched by age to four controls who were not exposed (n = 74,188). The main outcome measures were the risk of developing fibromyalgia and CFS. These were presented as adjusted incidence rate ratios (aIRR) with 95% confidence intervals (CIs). We found that 97 women in the exposed group developed fibromyalgia (incidence rate [IR] = 1.63 per 1,000 person-years) compared to 239 women in the unexposed group (IR = 0.83 per 1,000 person-years). Following adjustment, this translated to an IRR of 1.73 (95% CI = [1.36, 2.22]). Similarly, 19 women developed CFS in the exposed group (IR = 0.32 per 1,000 person-years), compared to 53 in the unexposed group (0.18 per 1,000 person-years), which translates to an aIRR of 1.92 (95% CI = [1.11, 3.33]). Therefore, we have identified an association between a history of IPV in women and the development of these functional syndromes, which may provide more information to inform the biopsychosocial pathway precipitating the development of fibromyalgia and CFS.